Essay Assessment toward Determining the Writing Proficiency Level of STEM, HUMSS, and ABM Twelfth Graders - Agbayani, Richard (International Journal of Language and Literary Studies, 2022)
This descriptive- quantitative study is attached to the principles of Process and Product, and Error Analysis Approaches. Its ultimate aim is to identify the writing proficiency level of students enrolled in STEM, HUMSS, and ABM K-12 tracks. Significant differences among the three groups were also ascertained. In doing so, 75 Grade 12 students with 25 students from each of the three tracks took part who were tasked to develop an essay on a given topic. The evaluation was guided by the rubrics introduced by Robitaille and Connelly (2002) and its foci revolved on five components that include content, organization, vocabulary, language use, and mechanics Participation of two inter- raters was also be sought. The written outputs’ assessment revealed that with regard to content and organization, the three groups recorded a good to average writing proficiency level. The vocabulary proficiency noted down a fair to poor remark for STEM students, whereas good to average description was obtained by HUMSS and ABM students. Further, regarding language use, both STEM and ABM students have fair to poor adeptness, while HUMSS group was good to average. As to mechanics component, HUMSS students documented an excellent to very good proficiency while STEM and ABM students’ status is fair to poor. Overall, there is a significant difference among or within the three groups